Effects of ion beam irradiation on agronomic traits and blast resistance in rice, and molecular screening of blast resistance genes - Parpaei, Soolmaz (2012)
Rice, Oryzasativa, is one of the most important food crops all over the world. Application of ion beam is one of the effective tools to induce mutations into the rice crops. Rice blast caused by, Pyricularia oryzae (Cooke) Sacc.,Teleomorph, Magnaporthe Oryzae isone of the most devastating diseases causing huge losses annuallyworldwide.Cultivating resistant cultivars is the most reliable method to prevent occurring blast disease in rice producing areas. Ion beam irradiation also can be utilized to improve desired agronomic traits that are related to rice yield. Plants performing desired characteristics should be cultivated for at least seven generations in order to obtain pure lines. M2 population of seeds MR219 (irradiated by Agency Nuclear Malaysia at three different doses of 40Gy, 60Gy, and 80 Gy) were used in this studyfor the effect of ionizing radiation. The study was related to the performance of M2 population for improvement of agronomic traits and severity screening of blast disease. Ten replications, including 20 samples in each replication were cultivated for the screening the variation of agronomic traits. The result of ANOVA revealed that there was a significant difference among treatments for all characteristics. The coefficient of variation for culm height, number of tillers, and number of panicles were higher than the control plants, which confirm the occurrence of mutation regarding to these characteristics. The highest variation for culm height was observed in 40 Gy dose of ion beam irradiation (10.16%). However, for number of tillers the highest variation was observed in 60 Gy and 80 Gy treatments, 38.14%, 41.49% respectively. In both these treatments maximum tiller number were observed. The highest variation for number of panicles belonged to 80 Gy (50.02%) and 14.26% among 40 Gyfor panicle length. However, for 1000-grain weight the variation was observed almost the same among different treatments. Generally, the high frequency of probable mutation was obtained for culm height.Three replications with 100 plants (samples) in each replication were evaluated for blast severity. 40Gy mutants showed the highest frequency rate in scoring index 1. 95% of plants with scoring 7 which showed the highest susceptibility was observed in 80 Gy treatment. 30 of the plants, which had shown the highest resistance to blast, were chosen for molecular evaluation using nineSimple Sequence Repeat (SSR) primer pairs. MR219 (control) and PS2 (resistant variety to blast) were used as controls for the evaluation. There was no variation observed fromthe results of SSR markers specific to blast resistance. MR219 variety was found to be a moderately tolerant line to blast disease.